A Combined Approach on RBC Image Segmentation through Shape Feature Extraction. (29th March 2012) - Wang, Ruihu; Fang, Bin
Abstract : The classification of erythrocyte plays an important role in clinic diagnosis. In terms of the fact that the shape deformability of red blood cell brings more difficulty in detecting and recognize for operating automatically, we believed that the recovered 3D shape surface feature would give more information than traditional 2D intensity image processing methods. This paper proposed a combined approach for complex surface segmentation of red blood cell based on shape-from-shading technique and multiscale surface fitting. By means of the image irradiance equation under SEM imaging condition, the 3D height field could be recovered from the varied shading. Afterwards the depth maps of each point on the surfaces were applied to calculate Gaussian curvature and mean curvature, which were used to produce surface-type label image. Accordingly the surface was segmented into different parts through multiscale bivariate polynomials function fitting. The experimental results showed that this approach was easily implemented and promising.